Effect of Stromal Vascular Fraction and Platelet-Rich Plasma Combination on Polymorphonuclear Cells in Wistar Rats Anal Trauma Model - Erwin Chandra; Sulmiati Sulmiati; Nita Mariana; Fonny Josh; Sachraswaty Rachman; Firdaus Hamid (Nusantara Medical Science Journal, 2022)
Introduction: By relying on polymorphonuclear (PMN) cells, stromal vascular fraction (SVF) and platelet-rich plasma (PRP) contribute significantly in the healing process. Through anal trauma model, this study examined the effect of SVF and PRP combination on PMN counts in vivo. Method: Three groups of twenty-eight eligible Wistar rats anal trauma model randomly assigned to receive SVF and PRP combination (Group A), normal saline (Group B), or healthy controls (Group C). On days 1, 7, and 14, we examined at PMN cell counts in Groups A and B. Group C were sacrificed early to acquire baseline data on PMN cells. Results:  On the first day, Group A had more PMN cells than Group B, but this difference faded by days 7 and 14. On day 1, the test revealed a significant increase in PMN cells (p=0.002). Conclusion:  Combining SVF and PRP can improve PMN cells' acute phase of anal damage repair in vivo